Promising new drugs and therapeutic approaches for treatment of ovarian cancer—targeting the hallmarks of cancer - Julia Hillmann; Nicolai Maass; Dirk O. Bauerschlag; Inken Flörkemeier (BMC Medicine)
Abstract Ovarian cancer remains the most lethal gynecological malignancy. Despite the approval of promising targeted therapy such as bevacizumab and PARP inhibitors, 5-year survival has not improved significantly. Thus, there is an urgent need for new therapeutics. New advancements in therapeutic strategies target the pivotal hallmarks of cancer. This review is giving an updated overview of innovative and upcoming therapies for the treatment of ovarian cancer that focuses specific on the hallmarks of cancer. The hallmarks of cancer constitute a broad concept to reenact complexity of malignancies and furthermore identify possible targets for new treatment strategies. For this purpose, we analyzed approvals and current clinical phase III studies (registered at ClinicalTrials.gov (National Library of Medicine, National Institutes of Health; U.S. Department of Health and Human Services, 2024)) for new drugs on the basis of their mechanisms of action and identified new target approaches. A broad spectrum of new promising drugs is currently under investigation in clinical phase III studies targeting mainly the hallmarks “self-sufficiency in growth signals,” “genomic instability,” and “angiogenesis.” The benefit of immune checkpoint inhibitors in ovarian cancer has been demonstrated for the first time. Besides, targeting the tumor microenvironment is of growing interest. Replicative immortality, energy metabolism, tumor promoting inflammation, and the microbiome of ovarian cancer are still barely targeted by drugs. Nevertheless, precision medicine, which focuses on specific disease characteristics, is becoming increasingly important in cancer treatment. Graphical Abstract